Trends and Issues in the Use of Garlic as A Natural Treatment for Lowering Blood Pressure in Hypertension Sufferers: Literature Review - Sari, Putri Irwanti; Junizar, Hasny Dwi; Hamidah, Hamidah; Siregar, Indah Awaliyah; Martawinarti, Rts Netisa Martawinarti; Mutmainnah, Muthia; Yusnilawati, Yusnilawati (Program Studi Keperawatan Universitas Jambi, 2025)
Introduction: Hypertension, or high blood pressure, is a global health problem whose prevalence continues to increase from year to year. The World Health Organization (WHO) reports that hypertension is one of the leading causes of death from cardiovascular disease worldwide. According to WHO data, approximately 1.28 billion adults aged 30–79 years suffer from hypertension globally. One natural ingredient that has attracted attention in the treatment of hypertension is garlic (Allium sativum). Thus, this paper aims to examine the effectiveness of garlic as a blood pressure-lowering drug in patients with hypertension and its underlying mechanism of action. Methods: A comprehensive review of relevant studies was conducted, analyzing findings related to hypertension management, barriers to treatment, and the role of healthcare professionals and complementary therapies in improving patient compliance. This study used search engines and databases. Result: The analyzed research findings consistently demonstrate that garlic has significant potential in lowering blood pressure among individuals with hypertension. Conclusion: Garlic (Allium sativum Linn.) has proven to be significantly effective in reducing blood pressure among hypertensive patients in various preparations such as extracts, decoctions, and infusions, primarily through the action of allicin as a vasodilator, antioxidant, and anti-inflammatory agent.